Human Colorectal Cancers with an Intact p16/Cyclin D1/pRb Pathway Have Up-Regulated p16 Expression and Decreased Proliferation in Small Invasive Tumor Clusters - Palmqvist, Richard (American Society for Investigative Pathology, 2000)
A systematic spatial heterogeneity with high proliferative activity at the luminal border and low activity at the invasive margin is an unexpected behavior that has been observed in colorectal cancer (CRC). To clarify this phenomenon and possible underlying regulatory mechanisms, we have by immunohistochemistry elucidated the proliferative activity and the expression of G1/S regulatory proteins in small and large tumor cell clusters at the invasive margin in 97 CRCs. By identifying small tumor clusters at the tumor front, actually invading cancer cells could be characterized and analyzed separately. These cells could then be compared with the main tumor mass represented by the larger tumor clusters. The proliferation was significantly lower in small tumor clusters compared with larger clusters (P < 0.001) and the decrease in proliferation was correlated with a p16 up-regulation (r(s) = −0.41, P < 0.001). Interestingly, CRCs lacking p16 expression (18%) or tumors with other aberrations in the p16/cyclin D1/pRb pathway had a less pronounced decrease in proliferation between large and small clusters (P < 0.001), further strengthening the association between p16 and ceased proliferation at the invasive margin. This contrasts to tumors with low p27 or abnormal p53 levels showing sustained proliferation in small tumor clusters. Our findings imply that invading CRC cells generally have low proliferative activity, and this phenomenon seems to be mediated through p16 and the p16/cyclin D1/pRb pathway.